[Rezension von: Questione criminale e identità nazionale in Italia tra Otto e Novecento] - Capozzi, Franco (Crime, histoire & sociétés, 2021)
On 17 march 1861, Vittorio Emanuele II was proclaimed, "by the grace of God and will of the nation", first King of Italy. A month later, however, the rebel Carmine Donatelli "Crocco" seized and occupied (with his private army, made up of former Bourbon soldiers and armed peasants) the town of Melfi, where he was greeted as a liberator by the local population. Immediately after the unification, therefore, the Kingdom of Italy was plunged into a state of emergency, as public order and the stabi...